Identification of (CdSe)32 Structure in Microemulsion-based Synthesis for Solar Cell Applications - Saifful Kamaluddin, Muzakir; Rajan, Jose (2014)
We investigated the optical and physical properties of different ratio of (i) non-ionic sucrose ester S1670 surfactant, (ii) 1-heptanol and (iii) deionized water using polarizing optical microscope. Three stable phases have been identified; they are (i) lamellar phase lyotropic liquid crystal, (ii) microemulsion and (iii) emulsion. CdSe quantum dots (QDs) were successfully synthesized using microemulsion system consisting 40/50/10 weight % of surfactant, oil and water respectively. The extracted QDs were characterized using XRD, UV-Visible and photoluminescence spectroscopies, and transmission electron microscopy (TEM). A thermodynamically stable chemical structure of (CdSe)32 has been identified using first principle density functional theory (DFT) and emitting states of the structure was calculated.